A method of testing and a device for testing a battery
Patent Information
- Application Number
- CN202610930880.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-10-20
AI Technical Summary
[0003]然而,现有二电极测试多仅反映整体电化学响应,难以区分不同界面的贡献,且循环后拆解表征只能获得静态结果,易受拆解扰动、空气暴露及局部受压不均影响,导致界面演变过程、成分分布与性能变化之间缺乏真实对应关系
[0036]本发明提供的电池的测试方法,通过采用包括加压组件、密封腔体以及设置于加压组件与电池叠层之间的弹性导电层的测试装置,并将电池叠层置于密封腔体内,在可控压力下对电池叠层进行充放电循环测试,能够在较接近实际受压工况的条件下实时监测电池叠层内部的界面变化状态,同时同步记录电池的电化学性能参数,进而建立界面演变与电化学性能之间的对应关系,提升电池界面失效研究的真实性、准确性和分析深度。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, and in particular relates to a battery testing method and testing device. Background Technology
[0002] In the study of interface failure in solid-state batteries, electrochemical testing combined with post-cycle disassembly characterization is usually used to analyze the interface state between the electrode and the solid electrolyte.
[0003] However, existing two-electrode tests mostly reflect the overall electrochemical response and are difficult to distinguish the contributions of different interfaces. Furthermore, post-cycle disassembly characterization can only obtain static results, which are easily affected by disassembly disturbances, air exposure, and uneven local pressure, resulting in a lack of real correspondence between interface evolution, component distribution, and performance changes.
[0004] Therefore, improving the real-time performance, accuracy, and correlation analysis capabilities of solid-state battery interface failure research under near-real-world pressure conditions has become an urgent technical problem to be solved. Summary of the Invention
[0005] The main objective of this invention is to provide a battery testing method and testing device. This battery testing method enables dynamic research on the battery interface evolution process and its relationship with performance changes, thereby improving the real-time performance, accuracy, and correlation analysis capabilities of interface failure analysis.
[0006] In a first aspect, the present invention provides a battery testing method, which employs a battery testing device for testing, the battery testing device comprising:
[0007] A pressurization assembly for applying controlled pressure to battery stacks;
[0008] A sealed cavity is provided to house the battery stack and maintain an inert environment.
[0009] An elastic conductive layer is disposed between the pressurizing component and the battery stack;
[0010] The testing method includes:
[0011] The battery stack is placed in the sealed cavity, and the elastic conductive layer is disposed between the pressurizing component and the battery stack; a controllable pressure is applied to the battery stack by the pressurizing component;
[0012] During the battery charge-discharge cycle, the interface changes inside the battery stack are monitored in real time.
[0013] The electrochemical performance parameters of the battery were recorded simultaneously, and the correlation between interface changes and electrochemical performance was analyzed.
[0014] As described in the test method above, the pressurization assembly includes an upper top column and a lower top column, and a transparent observation window is provided in the center of the upper top column and the lower top column;
[0015] The testing method further includes: observing the interface changes inside the battery stack in real time through the transparent observation window.
[0016] As described above, the testing device further includes a three-electrode testing system, which includes a reference electrode, the interface of which is located on the side wall of the sealed cavity.
[0017] The testing method further includes: performing in-situ electrochemical impedance spectroscopy using the three-electrode testing system.
[0018] The testing method described above further includes: performing chemical analysis on the cross-section of the battery stack through the transparent observation window, wherein the chemical analysis includes using Raman spectroscopy mapping technology to plot the spatial distribution of interfacial by-reaction products.
[0019] As described in the test method above, the battery stack is a solid-state battery stack, and the negative electrode in the battery stack includes at least one of silicon-based negative electrode and tin-based negative electrode;
[0020] And / or, the electrode sheets in the battery stack are self-supporting film electrodes prepared using a dry electrode process.
[0021] Secondly, the present invention provides a testing apparatus for performing the testing method described above, comprising:
[0022] A pressurization assembly for applying controlled pressure to battery stacks;
[0023] A sealed cavity is provided to house the battery stack and maintain an inert environment.
[0024] An elastic conductive layer is disposed between the pressurization component and the battery stack.
[0025] In the testing apparatus described above, the elastic conductive layer is a conductive microporous metal mesh layer;
[0026] The pore size of the conductive microporous metal mesh layer is 1~2μm;
[0027] And / or, the thickness of the conductive microporous metal mesh layer is 0.1~0.5mm;
[0028] And / or, the material of the conductive microporous metal mesh layer includes at least one of stainless steel, titanium, copper, nickel, and aluminum.
[0029] As described above, the pressurization component includes an upper top column and a lower top column, with a transparent observation window located in the center of the upper top column and the lower top column. The transparent observation window is circular or square. The material of the transparent observation window includes at least one of sapphire, quartz glass, and acrylic sheet.
[0030] Preferably, the transparent observation window is circular, and the diameter of the transparent observation window is ≥5mm;
[0031] Alternatively, the transparent observation window may be square, and the side length of the transparent observation window may be ≥5mm.
[0032] In the testing apparatus described above, the material of the pressurizing component includes at least one of stainless steel and titanium alloy;
[0033] And / or, the sealed cavity is enclosed by a sealed cavity frame, the material of which includes at least one of polyetheretherketone, polyimide, and polytetrafluoroethylene.
[0034] The testing device described above further includes a three-electrode testing system, which includes a reference electrode. The interface of the reference electrode is located on the side wall of the sealed cavity and is led out through a metal wire.
[0035] The metal wire includes at least one of indium wire, nickel wire, and platinum wire.
[0036] The battery testing method provided by this invention employs a testing device including a pressurizing component, a sealed cavity, and an elastic conductive layer disposed between the pressurizing component and the battery stack. The battery stack is placed in the sealed cavity, and charge-discharge cycle tests are performed on the battery stack under controllable pressure. This method can monitor the interface changes inside the battery stack in real time under conditions that closely resemble actual pressure conditions, and simultaneously record the battery's electrochemical performance parameters. This establishes a correlation between interface evolution and electrochemical performance, improving the authenticity, accuracy, and analytical depth of battery interface failure research. Attached Figure Description
[0037] To more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the accompanying drawings used in the description of the embodiments of the present invention or related technologies are briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0038] Figure 1 A schematic diagram of the structure of a battery testing device provided by the present invention;
[0039] Figure 2A scanning electron microscope image of a battery stack before cycling, provided for the present invention;
[0040] Figure 3 A scanning electron microscope image of a battery stack charged to 4.2V, provided for the present invention;
[0041] Figure 4 An electrochemical curve of a working electrode and a counter electrode provided for this invention;
[0042] Figure 5 A Raman spectrum provided for this invention;
[0043] Figure 6 A Raman image of a battery stack before cycling, provided by the present invention;
[0044] Figure 7 This invention provides a Raman image of a battery stack charged to 4.2V. Attached Figure Description
[0045] 1: Fixing screw; 2: Pressurization assembly; 21: Upper top post; 22: Lower top post; 3: O-ring; 4: Battery stack; 5: Transparent observation window; 6: Flat head screw; 7: Elastic conductive layer; 8: Sealed cavity frame; 9: Reference electrode; 10: Sealed cavity. Detailed Implementation
[0046] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0047] In existing technologies, the analysis of battery interface states typically employs a disassembly-based characterization approach. Specifically, researchers first mount the battery stack into a test fixture or button cell, subject it to charge-discharge cycles under a certain external pressure, and simultaneously record the overall electrochemical response, including voltage, current, capacity, and impedance. After cycling, the sample is disassembled, and the presence of cracks, pores, delamination, and byproduct accumulation at the interface is determined through microscopic morphology observation, component analysis, or cross-sectional testing. The basic principle of this approach is to use macroscopic electrochemical results to reflect changes in the overall battery performance, and then use post-processing characterization to infer the causes of interface failure.
[0048] However, this approach has significant limitations: traditional pressurization methods often result in uneven local pressure due to microscopic irregularities at the contact surface, leading to significant non-uniformity in interface damage and side reactions, which in turn causes the observed results to deviate from actual operating conditions. The direct consequence of this is that it is difficult to establish a true, consistent, and repeatable correspondence between interface changes, chemical composition distribution, and electrochemical performance parameters, limiting the depth of research on battery interface failure mechanisms and its engineering guidance value.
[0049] Therefore, how to observe the changes in the internal interface of the battery stack in real time under near-real pressure conditions, and to synchronously correlate and analyze the interface changes with electrochemical performance, has become an urgent technical problem to be solved.
[0050] Through extensive research, the inventors of this application discovered that by setting an elastic conductive layer between the pressurizing component and the battery stack, and then applying controllable pressure to the battery stack through the pressurizing component, the battery stack can be charged and discharged under stable pressure. During the cycling process, the interface change state inside the battery stack is monitored in real time, and the electrochemical performance parameters of the battery are recorded simultaneously, which allows for further analysis of the correlation between the battery interface change state and electrochemical performance.
[0051] In view of this, in a first aspect, the present invention provides a battery testing method, which uses a battery testing device for testing, such as... Figure 1 As shown, the battery testing apparatus includes: a pressurizing component 2 for applying controllable pressure to the battery stack 4; a sealed cavity 10 for containing the battery stack 4 and maintaining an inert environment; and an elastic conductive layer 7 disposed between the pressurizing component 2 and the battery stack 4. The testing method includes: placing the battery stack 4 in the sealed cavity 10 and disposing of the elastic conductive layer 7 between the pressurizing component 2 and the battery stack 4; applying controllable pressure to the battery stack 4 through the pressurizing component 2; monitoring the interface change state inside the battery stack 4 in real time during the battery charge-discharge cycle; synchronously recording the electrochemical performance parameters of the battery and analyzing the correlation between the interface change state and the electrochemical performance.
[0052] In this invention, by enclosing the battery stack 4 in a sealed cavity 10 and maintaining an inert environment, the interference of air and moisture on the active interface can be reduced, making the test results closer to the actual working state. An elastic conductive layer 7 is disposed between the pressurizing component 2 and the battery stack 4, which can compensate for the micro-undulations of the contact surface while conducting current, transforming "point-line contact" into uniform "surface-to-surface contact," thereby improving the uniformity of pressure and the stability of interface contact. The elastic conductive layer 7 can effectively disperse pressure, eliminate local stress concentration, prevent false alarms caused by abnormal failures, avoid the breakage of active materials or penetration of the electrolyte layer due to local overpressure, significantly improve the reliability of interface evolution in in-situ observations, and achieve high test repeatability.
[0053] The pressurization component 2 applies controllable pressure, causing the battery stack 4 to cycle under conditions close to the actual assembly pressure. This more realistically reflects the interfacial contact evolution, crack initiation, and side reaction development process. During cycling, the interfacial changes are monitored in real time, and electrochemical performance parameters such as voltage, capacity, and impedance are recorded simultaneously. Therefore, a correlation between interfacial evolution and performance degradation can be established, improving the real-time performance, accuracy, and repeatability of interfacial failure analysis. This provides a basis for material selection, structural design, and pressure window optimization.
[0054] Therefore, the battery testing method provided by the present invention, by employing a testing device including a pressurizing component 2, a sealed cavity 10, and an elastic conductive layer 7 disposed between the pressurizing component 2 and the battery stack 4, and placing the battery stack 4 inside the sealed cavity 10, performs charge-discharge cycle tests on the battery stack 4 under controllable pressure. This method can monitor the interface change state inside the battery stack in real time under conditions that are closer to actual pressure conditions, and simultaneously record the electrochemical performance parameters of the battery. This establishes a correspondence between interface evolution and electrochemical performance, thereby improving the authenticity, accuracy, and analytical depth of battery interface failure research.
[0055] In some embodiments of the present invention, the pressurizing component 2 includes an upper top column 21 and a lower top column 22, and a transparent observation window 5 is provided in the center of the upper top column 21 and the lower top column 22; the testing method also includes: observing the interface change state inside the battery stack 4 in real time through the transparent observation window 5.
[0056] With a transparent observation window 5 positioned in the center of the upper top column 21 and the lower top column 22, a continuous visual path is provided for optical observation while maintaining controllable pressure on the battery stack 4. This allows for direct acquisition of information on interface contact, crack initiation, delamination propagation, and local morphological changes without disassembling the sample or disrupting the sealed environment. Real-time observation of the interface changes within the battery stack 4 through the transparent observation window 5 enables synchronous tracking of the interface evolution process with the charging and discharging process. This reduces mechanical disturbances, air exposure, and result distortion caused by disassembly and transfer, thus facilitating a more realistic reflection of the dynamic failure behavior of the battery's internal interface under pressure conditions and improving the accuracy and repeatability of the correlation analysis between interface changes and electrochemical performance.
[0057] In some embodiments of the present invention, the testing device further includes a three-electrode testing system, which includes a reference electrode 9, the interface of which is located on the side wall of the sealed cavity 10; the testing method further includes: performing in-situ electrochemical impedance spectroscopy using the three-electrode testing system.
[0058] The interface of the reference electrode 9 is located behind the side wall of the sealed cavity 10. This allows the reference electrode 9 to be introduced while maintaining the cavity's seal and inert environment. This enables the three-electrode testing system to stably acquire the electrochemical responses of each electrode relative to the reference electrode 9 during the pressure, charge / discharge, and interface evolution processes of the battery stack 4. In-situ electrochemical impedance spectroscopy (EIS) using the three-electrode testing system can further decompose the overall battery coupling impedance and identify the contributions of different interfaces. This allows for a more accurate characterization of the impedance changes at the interfaces between the positive electrode and the solid electrolyte, and between the negative electrode and the solid electrolyte. It also allows processes such as interface contact degradation, crack propagation, and side reaction formation to correspond synchronously with impedance spectral characteristics, thereby improving the real-time performance, accuracy, and repeatability of interface failure mechanism analysis. Therefore, this is beneficial for material selection, structural design, and pressure window optimization.
[0059] Specifically, the upper top column 21 and the lower top column 22 can be used as current collectors, and the upper top column 21 and the lower top column 22 can be connected to an external electrochemical workstation through wires to form a three-electrode testing system.
[0060] Reference electrode 9 can be a lithium-based reference electrode.
[0061] In some embodiments of the present invention, the method further includes: performing chemical analysis on the cross-section of the battery stack 4 through the transparent observation window 5, wherein the chemical analysis includes using Raman spectroscopy mapping technology to plot the spatial distribution of interfacial side reaction products.
[0062] Chemical analysis of the cross-section of the battery stack 4 under pressure can be directly performed through the transparent observation window 5. This allows for the acquisition of compositional information in the interfacial region without disassembling the sample, avoiding contamination and disturbance introduced by transfer, exposure, and sample preparation, ensuring the data's accuracy and reliability. Raman spectroscopy mapping technology can scan interfacial byproducts (such as Li₂S) point-by-point and generate spatial distribution maps, thus characterizing the enrichment location, expansion range, and non-uniform distribution characteristics of byproducts at the interface between the positive electrode and the solid electrolyte or between the negative electrode and the solid electrolyte. This chemical distribution result corroborates real-time observations of cracks, delamination, and contact degradation, enabling a synchronous correlation between interfacial morphology evolution and the chemical failure process. Furthermore, it establishes a correspondence with changes in voltage, capacity, and impedance, thus facilitating more accurate identification of the main causes of interfacial failure and improving the accuracy and repeatability of mechanistic analysis.
[0063] In some embodiments of the present invention, the battery stack 4 is a solid-state battery stack, and the negative electrode in the battery stack 4 includes at least one of silicon-based negative electrode and tin-based negative electrode.
[0064] In some embodiments, the electrode sheet in the battery stack 4 is a self-supporting film electrode prepared using a dry electrode process.
[0065] When solid-state battery stacking is used and silicon-based and / or tin-based anodes are selected, targeted tests can be conducted on contact degradation, crack propagation and side reactions that are more likely to occur between the anode with large volume changes and the solid electrolyte, thereby more realistically characterizing the interface failure process.
[0066] When the electrode sheet is fabricated using a dry electrode process to create a self-supporting film electrode, no metal current collector is required.
[0067] This reduces the additional interference to the interface caused by residual solvents from wet processing, binder migration, and pore structure fluctuations, resulting in higher electrode structure stability and interface consistency. This, in turn, improves the repeatability of pressure cycling and in-situ observation results. Therefore, the aforementioned negative electrode system and the self-supporting membrane electrode configuration allow interface changes to more closely approximate actual solid-state battery operating conditions and establish a more reliable correspondence with simultaneously obtained electrochemical parameters, providing a basis for failure mechanism analysis and structural optimization.
[0068] Secondly, the present invention provides a testing apparatus for performing the testing method described above, such as... Figure 1 As shown, it includes: a pressurizing component 2 for applying controllable pressure to the battery stack 4; a sealed cavity 10 for accommodating the battery stack 4 and maintaining an inert environment; and an elastic conductive layer 7 disposed between the pressurizing component 2 and the battery stack 4.
[0069] In this invention, the elastic conductive layer 7 is used to achieve conductive connection between the battery stack 4 and the pressurizing component 2 during pressure transmission and to homogenize the contact pressure.
[0070] In this invention, the pressurizing component 2 refers to a clamping mechanism capable of applying and adjusting the load on the battery stack 4 along a predetermined pressure direction. Its function is to provide stable and repeatable stacking pressure for battery testing, simulating the pressure conditions of the battery under actual service conditions, and providing a controllable external boundary for changes in interface contact states. The pressurizing component 2 is typically arranged above and / or below the sealed cavity 10, allowing pressure to be transmitted along the thickness direction of the battery stack 4 to the layered structure composed of the positive electrode, solid electrolyte, and negative electrode. In specific implementations, the pressure applied to the battery stack 4 by the pressurizing component 2 can be adjusted by rotating the fixing screw 1.
[0071] The pressurization component 2 can provide uniform and adjustable stacking pressure (pressure range of 0~100MPa) to simulate the actual operating conditions of the battery.
[0072] The sealed cavity 10 refers to the shell structure used to enclose and maintain the internal inert atmosphere of the battery stack 4. Its function is to isolate air, moisture and other external contaminants, preventing oxidation, hydrolysis, moisture absorption or interface contamination of water-sensitive sulfide solid electrolytes, halide solid electrolytes and negative electrode materials with large volume changes during the test, thereby ensuring that the observed interface failure behavior is representative of real operating conditions. The sealed cavity frame 8 forms a relatively closed test space around the battery stack 4 and cooperates with the pressurization component 2 to define the pressure area, enabling the sample to be assembled, cycled and characterized under pressure.
[0073] The elastic conductive layer 7 is a conductive dielectric layer disposed between the pressurizing component 2 and the battery stack 4. It is capable of reversible elastic deformation under pressure while maintaining current conduction. Its function is twofold: firstly, to more smoothly transfer the external load applied by the pressurizing component 2 to the battery stack 4; and secondly, to compensate for contact differences caused by microscopic unevenness on the surface of the battery stack 4, thereby reducing local stress concentration, improving the contact uniformity between the electrode and the solid electrolyte, and between the battery stack 4 and the test end, and providing a stable conductive path for electrical signal acquisition during the test process. The elastic conductive layer 7 is sandwiched between the contact surfaces of the pressurizing component 2 and the battery stack 4, forming an interface with the upper and lower surfaces of the battery stack 4. This allows it to perform both conductive contact and pressure equalization and contact compensation under pressure, making it particularly suitable for silicon-based, tin-based, and other negative electrode systems with large volume changes, as well as sulfide and halide solid electrolyte systems that are sensitive to contact.
[0074] The battery testing device provided by this invention includes a pressurizing component 2, a sealed cavity 10, and an elastic conductive layer 7 disposed between the pressurizing component 2 and the battery stack 4. The battery stack 4 is placed in the sealed cavity 10, and charge-discharge cycle tests are performed on the battery stack 4 under controllable pressure. It can monitor the interface change state inside the battery stack in real time under conditions that are close to actual pressure conditions, and simultaneously record the electrochemical performance parameters of the battery. This establishes a correspondence between interface evolution and electrochemical performance, thereby improving the authenticity, accuracy, and analytical depth of battery interface failure research.
[0075] In some embodiments of the present invention, the elastic conductive layer 7 is a conductive microporous metal mesh layer; the pore size of the conductive microporous metal mesh layer is 1~2μm, for example, it can be a range of 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2μm or any two of them.
[0076] In some embodiments, the thickness of the conductive microporous metal mesh layer is 0.1 to 0.5 mm, for example, it can be a range of 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm or any two of these.
[0077] In some embodiments, the conductive microporous metal mesh layer is made of at least one of stainless steel, titanium, copper, nickel, and aluminum.
[0078] The conductive microporous metal mesh layer is a porous metal structure layer that combines elastic support, pressure homogenization, and conductive transmission functions. Its role is to diffuse the localized load applied by the pressurizing component 2 into a more uniform surface load when located between the pressurizing component 2 and the battery stack 4, and to establish a stable conductive path through the metal framework, thereby improving the electrical contact between the pressurizing component 2 and the battery stack 4. This conductive microporous metal mesh layer is typically disposed at the contact interface between the pressurizing component 2 and the battery stack 4, serving as an intermediate transition layer sandwiched or attached to the surface of the pressurizing component 2, and in direct or indirect contact with the battery stack 4 to achieve load transfer and conductive connection. Its pore size is 1~2μm to form a micropore scale conducive to pressure homogenization and contact adjustment; its thickness is preferably 0.1~0.5mm to provide sufficient mechanical support and conductive continuity while maintaining elasticity; its area is usually slightly larger than the effective pressure-bearing area of the sample to avoid edge pressure leakage or insufficient contact. The conductive microporous metal mesh layer can be a single-layer planar mesh sheet, a flexible mesh strip that has been rolled or calendered, or a porous metal sheet formed by multi-layer stacking or composite sintering. Its material can be at least one of stainless steel, titanium, copper, nickel, and aluminum. Stainless steel is suitable for balancing strength and corrosion resistance, titanium is suitable for high stability environments, copper or nickel is suitable for improving conductivity, and aluminum is suitable for reducing weight.
[0079] In some embodiments of the present invention, the pressurizing component 2 includes an upper top column 21 and a lower top column 22, with a transparent observation window 5 provided in the center of the upper top column 21 and the lower top column 22. The transparent observation window 5 is circular or square. The material of the transparent observation window 5 includes at least one of sapphire, quartz glass, and acrylic sheet. Preferably, the transparent observation window 5 is circular, and the diameter of the transparent observation window 5 is ≥5mm, for example, it can be a range of 5mm, 6mm, 7mm, 8mm, 9mm, 10mm, 15mm, 20mm or any two of them; or, the transparent observation window 5 is square, and the side length of the transparent observation window 5 is ≥5mm, for example, it can be a range of 5mm, 6mm, 7mm, 8mm, 9mm, 10mm, 15mm, 20mm or any two of them.
[0080] In this invention, the transparent observation window 5 is fixed to the middle of the sealed cavity frame 8 by a flat-head screw 6. It serves as a pressure-resistant, light-transmitting component providing an in-situ optical observation channel. While ensuring that the upper top column 21 and lower top column 22 apply axial pressure to the battery stack, it allows external imaging or observation equipment (e.g., optical microscope, confocal laser, or electron beam) to pass through the transparent observation window 5 to observe the internal interface of the battery stack 4 in real time. The transparent observation window can be a circular flat plate structure or a square flat plate structure. In one possible embodiment, a circular structure facilitates a more uniform stress distribution and rotationally symmetrical installation. In another possible embodiment, a square structure facilitates cooperation with a planar window seat and expands the imaging range. In yet another possible embodiment, the transparent observation window can also be installed using an embedded, press-fit, or screw-press fixing method.
[0081] The transparent observation window 5 can be made of at least one of sapphire, quartz glass, or acrylic sheet. Sapphire has high hardness, wear resistance, and pressure resistance, making it suitable for long-term observation under high load conditions. Quartz glass has good optical transmittance and thermal stability, making it suitable for scenarios with high requirements for imaging clarity and temperature adaptability. Acrylic sheet has the characteristics of convenient processing, low cost, and easier window size customization, making it suitable for scenarios with relatively low pressure requirements or verification experiments.
[0082] Preferably, when the transparent observation window 5 is circular, its diameter is not less than 5mm to ensure sufficient field of view and observation window area; when the transparent observation window 5 is square, its side length is not less than 5mm to meet the basic optical path requirements for microscopic imaging, video monitoring, or local area comparative observation; its thickness can be set according to the target pressure level, installation method, and light transmission requirements, and is usually matched with the window seat depth of the upper top column 21 and the lower top column 22 to avoid excessive local deflection or optical distortion during pressurization.
[0083] In this invention, O-rings 3 can be provided at both ends of the upper top post 21 and the lower top post 22 to ensure an inert environment inside the sealed cavity 10.
[0084] In some embodiments of the present invention, the material of the pressurizing component 2 includes at least one of stainless steel and titanium alloy.
[0085] In this invention, the material of the pressurizing component 2 can meet the requirements of high strength, pressure resistance, wear resistance, and corrosion resistance. Specifically, stainless steel can reduce friction and wear between the pressurizing component 2 and the elastic conductive layer 7, while titanium alloy can balance high specific strength and good chemical corrosion resistance.
[0086] In some embodiments, the contact surface between the pressurizing component 2 and the battery stack 4 may be plated with gold or carbon coating to prevent corrosion and reduce contact resistance.
[0087] In some embodiments, the sealed cavity 10 is enclosed by a sealed cavity frame 8, the material of which includes at least one of polyetheretherketone (PEEK), polyimide (PI), and polytetrafluoroethylene (PTFE).
[0088] The sealed cavity frame 8 is made of a corrosion-resistant and insulating material. Specifically, polyetheretherketone (PEEK) has high rigidity, which facilitates the formation of a stable mounting base; the polyimide insulating frame can balance temperature resistance and electrical insulation performance; and polytetrafluoroethylene (PTFE) can improve chemical inertness to sulfide electrolytes and related byproducts.
[0089] In some embodiments of the present invention, the testing device further includes a three-electrode testing system, which includes a reference electrode 9. The interface of the reference electrode 9 is located on the side wall of the sealed cavity 10 and is led out through a metal wire. The metal wire includes at least one of indium wire, nickel wire, and platinum wire.
[0090] In this invention, the three-electrode testing system is an electrochemical testing component used to extract the potential signals of the working electrode (upper top post 21 or lower top post 22), the counter electrode (upper top post 21 or lower top post 22), and the reference electrode 9 during the testing of the battery stack 4. Its purpose is to transmit the stable reference potential of the reference electrode 9 to external testing equipment while maintaining the inert environment and pressure state within the sealed cavity 10, thereby facilitating independent analysis of interface polarization, overpotential changes, and local reaction kinetics. The interface of the reference electrode 9 is preferably located in a reserved hole, insert groove, or sealed channel on the side wall of the sealed cavity 10, and is connected to the end of the reference electrode 9 inside the cavity. The outside is electrically connected to the reference channel of the electrochemical workstation via a metal wire, thus achieving signal extraction without compromising the cavity's sealing performance.
[0091] The interface of the reference electrode 9 can be configured as a through-type conductive terminal, an embedded metal sleeve interface, or a sealed wire connector. Through-type conductive terminals are suitable for compact cavities, embedded metal sleeve interfaces improve installation strength, and sealed wire connectors are more suitable for scenarios requiring easy assembly and replacement. The metal wire can be at least one of indium wire, nickel wire, or platinum wire in different embodiments. Indium wire has good plasticity and sealing adaptability, making it suitable for reliable contact with soft seals. Nickel wire combines high strength and conductivity, making it suitable for withstanding traction and slight bending during assembly. Platinum wire has excellent chemical inertness and electrochemical stability, making it suitable for testing environments with high signal stability requirements.
[0092] In this invention, the interface of the reference electrode 9 serves as an electrical signal channel between the sealed cavity 10 and external testing instruments. Its structure is defined as a conductive transition component disposed on the side wall of the sealed cavity 10 and connected to the internal reference electrode. Its function is to stably output the potential of the reference electrode 9 to the external testing system, enabling synchronous acquisition and comparative analysis of signals from the working electrode and the counter electrode. Positionally, the interface of the reference electrode 9 is typically located in the lower middle part of the side wall of the sealed cavity 10 or near the edge of the battery stack 4, to shorten the potential path from the reference electrode 9 to the interface under test and reduce lead voltage drop. During assembly, it can be reliably connected to the cavity side wall through threaded locking, crimping, welding, or embedded sealing, and an airtight seal is achieved through sealing rings, sealant, or metal gaskets.
[0093] The battery testing device provided by this invention can be equipped with an inert gas glove box adapter flange, enabling the entire process of assembly, testing, and disassembly under an inert atmosphere to be carried out in an oxygen-free and water-free environment, making it particularly suitable for air-sensitive sulfide systems. It can also be internally fitted with a pressure sensor component to achieve real-time monitoring of sample pressure changes. Furthermore, the testing device is small in size and can adapt to stress evolution under high-pressure environments.
[0094] The technical solution of the present invention will be further described below with reference to specific embodiments.
[0095] Example 1
[0096] The testing device in this embodiment is a battery testing device, such as... Figure 1 As shown, the device includes a pressurizing component 2; a sealed cavity 10; and an elastic conductive layer 7 disposed between the pressurizing component 2 and the battery stack 4. The elastic conductive layer 7 is a conductive microporous metal mesh layer made of stainless steel, with a pore size of 1.5 μm and a thickness of 0.3 mm. The pressurizing component 2 is made of stainless steel and includes an upper top post 21 and a lower top post 22. A transparent observation window 5 is provided in the center of the upper and lower top posts 21 and 22. The transparent observation window 5 is square (with a side length of 6 mm) and made of quartz glass. The sealed cavity 10 is enclosed by a sealed cavity frame 8 made of polyetheretherketone (PEEK). The testing device also includes a three-electrode testing system, which includes a reference electrode 9. The interface of the reference electrode 9 is located on the side wall of the sealed cavity 10 and is led out through an indium wire. The working electrode is the upper top post 21, and the counter electrode is the lower top post 22.
[0097] This embodiment aims to utilize the battery testing device of the present invention to monitor the interfacial mechanical failure behavior of the dry-prepared silicon-based anode during the charging and discharging process in real time, and directly reveal the causal relationship of "volume expansion-interfacial cracking-performance degradation".
[0098] The ternary cathode active material (LiNi) 0.8 Co 0.1 Mn 0.1 O2), halide solid electrolyte (Li2ZrCl6), vapor-grown carbon fiber (VGCF), and polytetrafluoroethylene (PTFE) were uniformly blended into powder in a mass ratio of 80:15:3:2. The powder was then repeatedly rolled and thinned to 91.2 μm under a pressure of 100 MPa to finally form a positive electrode film.
[0099] Silicon, sulfide solid electrolyte (Li6PS5Cl), vapor-grown carbon fiber (VGCF), and polytetrafluoroethylene (PTFE) were uniformly blended into powder at a mass ratio of 83:15:1:1. The powder was then repeatedly rolled and thinned to 24.0 μm under a pressure of 100 MPa to finally form a negative electrode film.
[0100] The sulfide solid electrolyte (Li6PS5Cl), the halide solid electrolyte (Li2ZrCl6), and polytetrafluoroethylene (PTFE) were uniformly blended into powder at a mass ratio of 98:2. The powder was then repeatedly rolled and thinned to 176.5 μm under a pressure of 100 MPa to finally form an electrolyte membrane.
[0101] The positive electrode membrane, electrolyte membrane, and negative electrode membrane are stacked in sequence and cut into semi-circles using a cutting die to form battery stack 4.
[0102] The battery stack 4 is placed inside the sealed cavity 10, and a controllable pressure is applied to the battery stack 4 through the pressurization component 2. An electrochemical workstation is then connected, and charge-discharge cycles are performed at a rate of 0.1C.
[0103] The test was paused at specific states of charge (SOC=0%, 50%, 100%), and the microstructure of the cross-section of the all-solid-state battery was directly photographed using a scanning electron microscope (SEM) through the transparent observation window 5.
[0104] Observation focus: Record the location of interface crack initiation, crack propagation rate, changes in electrode layer thickness, and loss of contact area caused by silicon particle expansion.
[0105] Advantages: It enables "synchronous in-situ electrochemical imaging," providing a direct view of the dynamic evolution of the internal structure of all-solid-state batteries during cycling, and directly confirming that interface failure is the main cause of performance degradation. The presence of the elastic conductive layer 7 reduces cracking caused by uneven pressure, improving test consistency.
[0106] Example 2
[0107] The testing apparatus for the battery in this embodiment is the same as that in Embodiment 1.
[0108] This embodiment aims to demonstrate the versatility of the battery testing device of the present invention in three-electrode testing and its pressure stability under three-electrode testing.
[0109] Cyclic testing: The battery stack 4 was assembled using the method of Example 1, with an indium wire as a reference electrode, and the battery stack 4 was charged to 4.2V (0.1C) under a stacking pressure of 50MPa.
[0110] Test data were collected using an electrochemical workstation.
[0111] Advantages: Impedance analysis: Through three-electrode EIS testing, it was successfully identified that the charge transfer impedance at the interface between the negative electrode and the electrolyte is the dominant factor in cycle failure, rather than the overall battery impedance.
[0112] Figure 4 The electrochemical curves of the working electrode and the counter electrode obtained from the test are shown.
[0113] Example 3
[0114] The testing apparatus for the battery in this embodiment is the same as that in Embodiment 1.
[0115] This embodiment aims to utilize the battery testing device of the present invention to conduct in-depth analysis of the spatial distribution of interfacial by-reaction products after cycling, and to reveal the chemical failure mechanism.
[0116] Cyclic testing: The battery stack 4 was assembled using the method of Example 1. Raman imaging and Raman spectra of the battery stack 4 before cycling were measured using a Raman spectrometer through a transparent observation window 5. The battery stack 4 was charged to 4.2V (0.1C) under a stacking pressure of 50MPa, and Raman imaging and Raman spectra of the battery stack 4 were measured again using a Raman spectrometer through a transparent observation window 5.
[0117] Specifically, the spatial resolution is set to ≤1μm, and the scan spans the entire interface area.
[0118] Characteristic peak identification: ~520cm -1 (crystalline Si), ~160-210 cm⁻¹ -1 &~705cm -1 (Li x Si): Mapping the negative electrode active material and degree of lithiation ( Figure 5 ).
[0119] Results Analysis: A two-dimensional chemical distribution thermogram was generated. The chemical composition change trend after charging to a 4.2V negative electrode at 50MPa pressure shows that Si at the interface is uniformly lithilated to form Li. x Si.
[0120] Advantages: Avoids localized lithium enrichment caused by uneven pressure. Simultaneously, it obtains accurate interfacial chemical maps, precisely pinpointing the source of failure and guiding interfacial modification strategies.
[0121] Figure 2 A scanning electron microscope image of a battery stack before cycling, provided for the present invention.
[0122] Figure 3 A scanning electron microscope image of a battery stack charged to 4.2V, provided for the present invention.
[0123] from Figure 2 and Figure 3 It can be seen that the pressure on the battery stack is relatively uniform, and no cracks have been generated.
[0124] Figure 5 This invention provides a Raman imaging mapping diagram of a battery stack before cycling.
[0125] Figure 6 This invention provides a Raman imaging mapping diagram of a battery stack charged to 4.2V.
[0126] Figure 7 A Raman spectrum provided for this invention.
[0127] from Figures 5-7 It can be seen that the lithiation process of silicon, the anode material, is relatively uniform.
[0128] The battery testing method provided by this invention employs a testing device including a pressurizing component, a sealed cavity, and an elastic conductive layer disposed between the pressurizing component and the battery stack. The battery stack is placed in the sealed cavity, and charge-discharge cycle tests are performed on the battery stack under controllable pressure. This method can monitor the interface changes inside the battery stack in real time under conditions that closely resemble actual pressure conditions, and simultaneously record the battery's electrochemical performance parameters. This establishes a correlation between interface evolution and electrochemical performance, improving the authenticity, accuracy, and analytical depth of battery interface failure research.
[0129] Finally, it should be noted that other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein, and is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.
Claims
1. A method for testing a battery, characterized in that, The battery is tested using a battery testing device, which includes: A pressurization assembly for applying controlled pressure to battery stacks; A sealed cavity is provided to house the battery stack and maintain an inert environment. An elastic conductive layer is disposed between the pressurizing component and the battery stack; The testing method includes: The battery stack is placed in the sealed cavity, and the elastic conductive layer is disposed between the pressurizing component and the battery stack; a controllable pressure is applied to the battery stack by the pressurizing component; During the battery charge-discharge cycle, the interface changes inside the battery stack are monitored in real time. The electrochemical performance parameters of the battery were recorded simultaneously, and the correlation between interface changes and electrochemical performance was analyzed.
2. The test method according to claim 1, characterized in that, The pressurization assembly includes an upper top column and a lower top column, and a transparent observation window is provided in the center of the upper top column and the lower top column; The testing method further includes: observing the interface changes inside the battery stack in real time through the transparent observation window.
3. The test method according to claim 1 or 2, characterized in that, The testing device also includes a three-electrode testing system, which includes a reference electrode, the interface of which is located on the side wall of the sealed cavity; The testing method further includes: performing in-situ electrochemical impedance spectroscopy using the three-electrode testing system.
4. The test method according to claim 2, characterized in that, Also includes: Chemical analysis of the cross-section of the battery stack is performed through the transparent observation window. The chemical analysis includes using Raman spectroscopy mapping technology to plot the spatial distribution of interfacial by-reaction products.
5. The test method according to any one of claims 1-4, characterized in that, The battery stack is a solid-state battery stack, and the negative electrode in the battery stack includes at least one of silicon-based negative electrode and tin-based negative electrode. And / or, the electrode sheets in the battery stack are self-supporting film electrodes prepared using a dry electrode process.
6. A testing apparatus for performing the testing method according to any one of claims 1-5, characterized in that, include: A pressurization assembly for applying controlled pressure to battery stacks; A sealed cavity is provided to house the battery stack and maintain an inert environment. An elastic conductive layer is disposed between the pressurization component and the battery stack.
7. The testing apparatus according to claim 6, characterized in that, The elastic conductive layer is a conductive microporous metal mesh layer; The pore size of the conductive microporous metal mesh layer is 1~2μm; And / or, the thickness of the conductive microporous metal mesh layer is 0.1~0.5mm; And / or, the material of the conductive microporous metal mesh layer includes at least one of stainless steel, titanium, copper, nickel, and aluminum.
8. The testing apparatus according to claim 6 or 7, characterized in that, The pressurization assembly includes an upper top column and a lower top column, with a transparent observation window located in the center of the upper and lower top columns. The transparent observation window is circular or square. The material of the transparent observation window includes at least one of sapphire, quartz glass, and acrylic sheet. Preferably, the transparent observation window is circular, and the diameter of the transparent observation window is ≥5mm; Alternatively, the transparent observation window may be square, and the side length of the transparent observation window may be ≥5mm.
9. The testing apparatus according to any one of claims 6-8, characterized in that, The pressurization component is made of at least one of stainless steel and titanium alloy; And / or, the sealed cavity is enclosed by a sealed cavity frame, the material of which includes at least one of polyetheretherketone, polyimide, and polytetrafluoroethylene.
10. The testing apparatus according to any one of claims 6-9, characterized in that, The testing device also includes a three-electrode testing system, which includes a reference electrode. The interface of the reference electrode is located on the side wall of the sealed cavity and is led out through a metal wire. The metal wire includes at least one of indium wire, nickel wire, and platinum wire.